Exploring the lived experiences of social media influencers in shaping halal consumer behavior through digital engagement - Razali, Mohammad Radfiq; Samori, Zakiah (Universiti Teknologi MARA (UiTM), Malaysia, 2025)
In the age of digital transformation, social media has emerged as a powerful platform influencing consumer behavior across various sectors, including the halal industry. This study aims to explore how social media influencers shape halal consumer behavior through digital engagement, focusing on the Malaysian context. Guided by a qualitative phenomenological design, in-depth semi-structured interviews were conducted with five Muslim influencers (n=5) and thematic analysis generated three overarching themes which are building consumer trust through original content, applying education strategies to develop halal consciousness and balancing moral imperatives in influencing purchase behavior. These findings enhance the knowledge of digital halal marketing and guide policymakers and marketers on how to align social media efforts with Islamic values. These insights contribute to a deeper understanding of ethical marketing in the halal ecosystem and highlight the strategic role influencers play in promoting Shariah-compliant consumerism.